Self-cycling redox nanoplatform in synergy with mild magnetothermal and autophagy inhibition for efficient cancer therapy. (April 2022) - Wang, Miao; Chen, Qian; Xu, Dong; Yang, Zebin; Chen, Jufeng; Zhang, Yang; Chen, Hangrong
Highlights: A self-cycling redox nanoplatform was developed to realize an efficient nanocatalytic therapy. The excellent magnetothermal performance of CuFe2 O4 NPs accelerates the production of ROS. Autophagy inhibitor, chloroquine, was integrated into mesoporous CuFe2 O4 NPs. The loading of chloroquine results in enhanced synergistic MHT-CDT by relieving autophagy. Graphical Abstract: ga1 Abstract: Magnetic hyperthermia and reactive oxygen species (ROS)-related nanocatalytic tumor therapy has received increasing focus due to their no penetration depth limit, tumor-specificity, and non-invasiveness. However, their efficacy is still affected by the intrinsic protective mechanism of cells' autophagy. Herein, a novel mesoporous magnetic copper ferrite nanoagent (CuFe2 O4 NPs) containing autophagy inhibitor chloroquine was developed for the synergistic enhancement of cancer treatment. Specifically, the mesoporous structured CuFe2 O4 NPs with high surface area was endowed with highly efficient ROS generation via self-cycling Fenton redox process between Cu 2+ and Fe 3+ . More importantly, the inside autophagy inhibitor chloroquine could efficiently inhibit cancer cells' resistance to hyperthermia and oxidative stress, realizing mild magnetic hyperthermia therapy (MHT) under 45 °C and preventing from damages to normal tissues. Furthermore, the temperature rise within tumor area further accelerated the Fenton reaction to boost the productivity of hydroxyl radicals (· OH) for enhancement of chemodynamic therapy (CDT). This work offers a novel strategy of magnetothermal-augmented in-situ self-cycling redox nanocatalysis in synergy with inhibition of autophagy, enlightening a new insight on the design of multifunctional therapeutic nanoagents based on a single component.